Laboratory Diagnosis of Tuberculous Meningitis – Is There a Scope for Further Improvement? - Thakur, Rajeev; Goyal, Renu; Sarma, Smita (Journal of Laboratory Physicians, 2010)
Aims: Tuberculous meningitis (TBM) still remains a diagnostic challenge because of inconsistent clinical presentation and lack of rapid, sensitive and specific tests. This study was carried out to diagnose TBM by a combination of direct microscopy on Ziehl-Neelsen (ZN) staining, culture by conventional Lowenstein Jensen (LJ) media and Bactec MGIT 960 system in clinically suspected cases, supported by laboratory parameters.Materials and Methods: A total of 164 cerebrospinal fluid (CSF) samples from suspected cases of TBM were processed for direct acid fast bacilli (AFB) smear examination, and culture on Bactec MGIT 960 and LJ media.Results: AFB were detected on direct smears in 13 of 164 (7.9%) specimens and Mycobacterium tuberculosis was isolated by at least one of the culture methods from 49 (29.8%) CSF samples, of which 45 (27.4%) were detected positive for M. tuberculosis by MGIT 960 culture and 18 (10.9%) by culture on LJ medium. The mean time of detection in MGIT and LJ media for M. tuberculosis were 18 and 38 days, respectively.Conclusions: A combination of laboratory parameters like smear microscopy, conventional culture and automated method like Bactec MGIT increases the sensitivity of diagnosing TBM as compared to any single method.
Keywords: Bactec MGIT 960; cerebrospinal fluid; tuberculous meningitis